Knowledge and Practices of Nurses Regarding Prevention of Surgical Site Infections in Tertiary Care Hospitals Peshawar: Knowledge and Practices of Nurses - Muhammad, Sohail; Khan, Muhammad Nasir; Haq, Sami Ul; Rahim, Muhammad (Pakistan Journal of Health Sciences, 2025)
Surgical procedures have many complications of which the leading one is post-surgical site infection (SSI), which can be prevented by following appropriate guidelines. SSI may lead to loss of body parts, septicemia and increase hospital bed occupancy. Objective: To assess nurses’ knowledge and practices regarding the prevention of surgical site infections in tertiary care hospitals in Peshawar. Methods: Descriptive cross-sectional study was conducted among 172 nurses recruited through convenient sampling. Study settings were two tertiary care hospitals in Peshawar. Data was collected through an adopted, self-administered questionnaire and were analyzed by SPSS version 26.0. Results: Findings of the study revealed that the knowledge level of the nurses was poor about the prevention of SSI, while their practice levels were also average. A significant difference was found in the knowledge level of the study participants on the basis of their gender with a p value; 0.001, qualification with a p value; 0.000. Years of experience with a p value; 0.007, and attending infection control courses with a p value; 0.03. In addition, a significant difference was found among the practices of nurses regarding the prevention of SSI on the basis of their gender with a p value; 0.012. Conclusion: The study’s findings revealed that nurses had a poor level of knowledge about SSI, while their practices were average according to arbitrary.